Comparative study of ZnO thin film prepared by pulsed laser deposition – Comparison of influence of different ablative lasers. (April 2017) - Bruncko, Jaroslav; Šutta, Pavol; Netrvalová, Marie; Michalka, Miroslav; Vincze, Andrej; Kovac, Jaroslav
Abstract: The contribution deals with transparent conductive oxides based on ZnO, which were prepared by Pulsed Laser Deposition (PLD) and their different properties are compared in the scope of the applied ablating lasers: (1) a solid state Nd:YAG laser working at third harmonic generation (wavelength 355 nm, 15 ns pulse length and 10 Hz pulsing frequency) and (2) an excimer laser working with KrF gas composition (248 nm, 20 ns and 10 Hz). The first part of the study deals with the influence of the oxygen pressure on crystallographic parameters of undoped ZnO films and the pressure interval between 2 and 5 Pa was assessed as an optimum. Moreover, the influence of different doping elements, aluminum and gallium, respectively, were analyzed. The results showed that a small amount (∼0.15% wt. content) of Al (or Ga, respectively) substantially improved carrier concentration with adequate resistivity decrease. Furthermore, optical properties: – transmittances and energy band-gap shift were investigated. Comparison between applied lasers revealed a substantially positive effect on electrical properties for the excimer laser. Moreover, acquired results showed that there is a complex dependence among chemical composition, growth conditions and final properties of the ZnO doped films which can be effectively controlled by using PLD. Highlights: Pulsed laser deposition of ZnO undoped and doped thin films. Influence of two ablative lasers were compared (Nd:YAG and excimer laser). Al and Ga was used as doping elements. High transparency of doped ZnO films – comparative results for both lasers. Electrical properties – more positive effect after application of excimer laser.